Droop control-based fast frequency support of wind power generation integrated grid-forming VSC-HVDC system - Chen, Qian; Shi, Gang; Lu, Yi; Qiu, Peng; Zhou, Jianqiao; Yang, Renxin; Zhang, Jianwen (Frontiers in Energy Research, 2024)
Current researches mainly focus on the participation of wind farms in primary frequency regulation, including overspeed load shedding control, propeller control and their coordinated control, etc. The frequency support is realized by reserving reserve capacity of wind turbines, but the influence of the dynamic characteristics of maximum power point tracking (MPPT) on the overall frequency regulation characteristics of wind turbines during frequency support is ignored. To this end, firstly, the frequency response model of the system is constructed, and the main factors that affect the frequency dynamic characteristics are revealed. Secondly, the principle of the grid-forming VSC with the function of self-inertial synchronization is introduced, the influence of the dynamic characteristics of MPPT on the frequency regulation characteristics of the wind turbine generator is clarified. Finally, based on the PSCAD/EMTDC electromagnetic transient simulation software platform, the influence of the dynamic characteristics of MPPT on the frequency regulation characteristics are verified by combining the inertia self-synchronous network control technology. The simulation results indicate that with the increase of setting of droop control, the decrease of output power of MPPT becomes large so as to weaken the frequency support capability.